Translation: From Bench to Brain – Using the visual arts and metaphors to engage and educate. (15th July 2017) - Jones, Rhys Bevan; Thomas, Julia; Lewis, Jamie; Read, Simon; Jones, Ian
Abstract : This article examines multidisciplinary public engagement projects that bring together developments in psychiatric research and practice with visual art and its use of metaphor. The article focuses on the art exhibition Translation: From Bench to Brain, which was the basis for further collaborations, illustrating how the learning from the original event influenced subsequent projects. Combining art exhibitions with online documentation and resources, the projects explored not only medical and scientific themes, but also the wider social, cultural and ethical ramifications, specifically aspects of identity, risk and stigma. The activities demonstrate the value of a developmental approach to public engagement as a process, whereby projects build on previous activities and evolving multidisciplinary perspectives, networks and expertise.